Pengaruh Cognitive Behavior Therapy terhadap Self Care Behavior Lansia dengan Hipertensi di Wilayah Kerja Puskesmas Buton Selatan - Harmanto Harmanto; Nana Supriyatna; Sigit Mulyono (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
After entering the elderly, a person will tend to experience changes in cognitive and psychomotor functions, the decline in cognitive aspects causes a decline in action and behavior of the elderly which includes learning, understanding, attention and understanding. One of the efforts to improve self-care behavior in hypertensive elderly is through Cognitive Behavioral Therapy (CBT). The purpose of this study identified the effect of cognitive behavior therapy on self-care behavior in elderly with hypertension. The research design was a quasi-experimental pre and post control group consisting of 18 respondents in the intervention group and 18 respondents in the control group who were not given intervention. The results showed that there was a significant effect of cognitive behavior therapy on elderly self-care behavior before and after participating in cognitive behavior therapy in the intervention group (p value = 0.000) and there was no effect of cognitive behavior therapy on elderly self-care behavior pre and post in the control group (p value = 0.163). Apart from cognitive behavior therapy, family history of hypertension also affects self-care behavior. Cognitive Behavioral Therapy (CBT) can be used as an action by nurses at health centers through home visits to hypertensive patients to reduce complications of disease complications and improve self-care behavior of elderly people with hypertension. Keywords: cognitive behavior therapy; elderly; hypertension; self-care behavior ABSTRAK Setelah memasuki masa lansia, seseorang akan cenderung mengalami perubahan fungsi kognitif maupun psikomotornya, penurunan aspek kognitif menyebabkan kemunduran aksi maupun perilaku dari lansia yang meliputi kegiatan belajar, pemahaman, perhatian dan pengertian. Salah satu upaya untuk meningkatkan self care behavior pada lansia hipertensi adalah melalui Cognitive Behavioral Therapy (CBT). Tujuan penelitian ini mengidentifikasi pengaruh cognitive behavior therapy terhadap self care behavior lansia dengan hipertensi. Desain penelitian ini adalah quasi eksperimen pre dan post with control group terdiri dari 18 responden kelompok intervensi dan 18 responden kelompok kontrol tidak diberikan intervensi. Hasil menunjukkan bahwa ada pengaruh cognitive behavior therapy terhadap self care behavior lansia sebelum dan sesudah mengikuti cognitive behavior therapy pada kelompok intervensi secara signifikan (p value = 0,000) dan tidak ada pengaruh cognitive behavior therapy terhadap self care behavior lansia pre dan post pada kelompok kontrol (p value =0,163). Selain cognitive behavior therapy, riwayat keluarga hipertensi juga mempengaruhi self care behavior. Cognitive Behavioral Therapy (CBT) dapat dijadikan tindakan oleh perawat di puskesmas melalui kunjungan rumah pada pasien hipertensi untuk menurunkan komplikasi komplikasi penyakit dan meningkatkan perilaku perawatan diri lansia dengan hipertensi. Kata kunci: cognitive behavior therapy; hipertensi; lansia; self care behavior